Gestión Contable y Tributaria del Comercial Wendy Cantón Ventanas - Izquierdo Lara, Jenny Zulay (2018)
Comercial Wendy is a small private company Obligated to Keep Accounting, whose ordinary business is focused more on the hardware sector, which is dedicated especially to the wholesale and retail of agricultural machinery and equipment including parts and pieces. It is the place where the present study case was made, with the topic ACCOUNTING AND TRIBUTARY MANAGEMENT OF THE WENDY CANTÓN VENTANAS COMMERCIAL, so that it allows to have a detailed knowledge about the control that is carried out in the ordinary activities that it carries out and its commitment fiscal. Additionally, it is located in the sub-line of investigation Management of accounting information. The consecutive research carried out was carried out with the following purpose, to be able to know the process that manages this business, when recording its daily activities, in order to determine if it is in accordance with the norms and laws, and check if you have an accounting system manually or through a computer program. In order to verify how this affects the tax and accounting part of the commercial. As a research method, to be able to carry out this case study, it was mainly oriented in the interview conducted with the accountant who provides services to the commercial, and the business owner. At the same time, information was provided on the forms, such as 104, 103, and 102. Additionally, bibliographic sources were used to help with the support of relevant information for this case. Regarding the limitations of this case study, they were the lack of an adequate accounting record, where the business is allowed to carry a certain classification of the accounting accounts to which it must possess as being obliged to keep accounts. However, each of the people who work in this business contributed with the required information requested.